How does life satisfaction change during the transition from school to work? A study of ninth and tenth-grade school-leavers in Germany - Siembab, Matthias [Verfasser]; Stawarz, Nico [Verfasser] (My University, 2019)
„We analyze how life satisfaction changes when adolescents leave school and enter the German vocational and educational training (VET) system. We draw on data from the German National Educational Panel Study (NEPS, Starting Cohort 4) and apply fixed effect regression models. Our findings suggest that leaving school and entering the VET system is associated with an increase in life satisfaction - regardless of the occupational status (i.e., whether the individual is in dual or school-based vocational training or in a vocational preparation program). Moreover, our results provide evidence that adolescents are “happy” to leave school; that having high self-esteem leads to a smaller increase in life satisfaction, and that reaching or failing one’s educational aspirations does not explain changes in life satisfaction.“ (authors’ abstract; BIBB-Doku)
Keywords: P 2.1 Schulabgänger; G 1.3.2.2 Übergänge; G 2.4.2 Lebenskonzepte, -stile, Werte; 370; 300; Jugendlicher; Schulabgänger; Berufseinmündung; Erste Schwelle; Zufriedenheit; Lebenssituation; Nationales Bildungspanel